The ultimate guide to weight training for rugby - Price, Robert G., ....- (2006)
The Ultimate Guide to Weight Training for Rugby is the most comprehensive and up-to-date rugby-specific training guide in the world today. It contains descriptions and photographs of nearly 100 of the most effective weight training, flexibility, and abdominal exercises used by athletes worldwide. This book features year-round rugby-specific weight-training programs guaranteed to improve your performance and get you results. No other rugby book to date has been so well designed, so easy to use, and so committed to weight training. This book will increase the players power and quickness resulting in more effectiveness in rucks and mauls. By using this program, you will make considerable gains in your strength, agility, and stamina which will result in more success in scrums and have you competing strong until the final whistle. Both beginners and advanced athletes and weight trainers can follow this book and utilize its programs. From recreational to professional, thousands of athletes all over the world are already benefiting from this book and its techniques, and now you can too!
Maximize your athletic potential! - Pre-season, in-season, and off-season sport-specific programs designed to: increase speed and power, eliminate fatigue and prevent injuries
Keywords: Rugby ; krachttraining